The Effect of Seaweed Soy Tempe Extract on the Reduction of Blood Sugar Levels in Alloxan Induced Rats (Mus musculus) - Abdul Hakim Laenggeng; Asriani Hasanuddin; Sitti Nuryanti; Manap Trianto (Postgraduate, University of Mataram, 2025)
Diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia due to impaired insulin secretion or action. This study aimed to examine the antihyperglycemic effect of seaweed soybean tempeh extract in alloxan-induced diabetic mice. A Completely Randomized Design (CRD) was used with 20 healthy male mice (2–3 months old, 25–30 g), divided into five groups: negative control, positive control (metformin), and three treatment groups receiving extract doses of 25, 75, and 125 mg/kg BW. Prior to treatment, mice underwent acclimatization to ensure uniform baseline conditions. Blood glucose levels were measured to assess the effects of the extract. Data were analyzed using ANOVA followed by the Least Significant Difference (LSD) test. The results showed that alloxan effectively induced hyperglycemia by damaging pancreatic beta cells. Administration of seaweed soybean tempeh extract significantly reduced blood glucose levels (p < 0.05). The highest dose (125 mg/kg BW) produced the most notable effect, comparable to metformin, while the 75 mg/kg BW dose also demonstrated significant efficacy. Both were significantly more effective than the lowest dose. In conclusion, seaweed soybean tempeh extract has potential as an alternative antihyperglycemic agent, especially at higher doses.